Nutrition a handbook for nurses - Best, Carolyn. (Wiley series in nursing., 2008)
This book provides a comprehensive look at all aspects of nutrition from roles and responsibilities to caring for a patient with specific nutritional needs. It is aimed primarily at nurses and addresses some of the issues they will encounter when caring for patients nutritional needs in a hospital setting. It also highlights the benefits of a hospital based Nutrition Team providing a multidisciplinary approach to nutrition. It includes a number of case studies to clarify some of the issues discussed and concludes by examining issues that need to be considered before discharging a patient home.